Perancangan Dan Implementasi Sistem Informasi Manajemen Proyek Berbasis Web Dengan Metode WATERFALL - Alfia Dwi Rahma; Chotijah, Umi (STMIK KAPUTAMA, 2024)
CV Winman Konstruksi is a company that focuses on the building construction sector. The portfolio of projects that CV Winman Konstruksi has successfully undertaken covers a wide range of work, from the planning stage to the implementation of building construction and repair projects. In conducting the project management process, CV Winman Konstruksi has been using personal short messages as a means of communication between employees, but it needs to be recognized that this method may have limitations in terms of progress tracking, project documentation, and building a formal framework that can provide more systematic and structured guidance for the entire project team. The result of this research is a computerized system as a means of project management which is realized in the form of a project management information system website. In developing this system, researchers use the waterfall method which consists of the stages of needs analysis, design, design, implementation and testing. Later it is hoped that with this system, the management process at the CV Winman Konstruksi company can be monitored easily anywhere and anytime.